2009
DOI: 10.2478/v10003-009-0012-6
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Radial Growth Reaction of Norway Spruce Along An Altitudinal Gradient in the Šumava Mountains

Abstract: Extreme radial growth reactions were analyzed over a 79-year period (1922-2000) to compare response of Norway spruce (Picea abies [L.] Karst.) along an altitudinal gradient (376-1221 m a.s.l.) in the Šumava Mountains, the Czech Republic. Extreme growth events were defined as pointer years, when an average percentage of the site pointer years reached at least 50% strength observed at the relevant altitudinal zone (low < ca. 700 m; middle ca. 700-950 m, high > ca. 950 m). The comparison of the pointer years sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…The finding that Norway spruce growth in the study area was mainly temperature-driven has been observed in other studies (Č ejková and Kolář, 2009;Treml et al, 2012;Wilson and Hopfmueller, 2001), although we found that growth was also influenced by spring precipitation. Even though we found similar patterns of the climate-growth relationships at the plot and tree scales, the individualistic approach highlighted that while most trees positively responded to spring precipitation, some of them also reacted to precipitation in previous and current summers.…”
Section: Comparisons Of the Responses Of Rwis To Climate At The Plot supporting
confidence: 72%
See 2 more Smart Citations
“…The finding that Norway spruce growth in the study area was mainly temperature-driven has been observed in other studies (Č ejková and Kolář, 2009;Treml et al, 2012;Wilson and Hopfmueller, 2001), although we found that growth was also influenced by spring precipitation. Even though we found similar patterns of the climate-growth relationships at the plot and tree scales, the individualistic approach highlighted that while most trees positively responded to spring precipitation, some of them also reacted to precipitation in previous and current summers.…”
Section: Comparisons Of the Responses Of Rwis To Climate At The Plot supporting
confidence: 72%
“…Norway spruce growth generally increases with summer temperature towards higher elevation and it is mainly constrained by low water availability at lower elevations (e.g. Büntgen et al, 2007;Č ejková and Kolář, 2009;Mäkinen et al, 2002;Treml et al, 2012;Wilson and Hopfmueller, 2001). Nevertheless, the sensitivity of Norway spruce RWIs to climate at different elevations was frequently modulated by other stand and tree features, such as stand crowding, tree-to-tree competition, or tree age.…”
Section: The Effect Of Elevation On the Norway Spruce Growth Responsementioning
confidence: 97%
See 1 more Smart Citation
“…climate), and it depends on tree species, bioclimatic regions, and site characteristics (Oberhuber et al, 1998;Desplanque et al, 1999;Rolland et al, 2000;Elferts, 2007). Pointer years are particularly useful for dendrochonological dating and they can be a powerful tool for dating the reaction of trees to climatic influences, particularly regarding extreme events (Desplanque et al, 1999;Vitas & Erlickytė, 2007) and at sites located at the ecological limits of the tree species (Rolland et al, 2000;Čejková & Kolář, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bigler et al, 2004;Gray et al, 2004;Muzika et al, 2004;Büntgen et al, 2006;Carrer and Urbinati, 2006;Koprowski and Zielski, 2006;Esper et al, 2007;Büntgen et al, 2007;Čejková and Kolář, 2009;Feliksik and Wilczyński, 2009;Bijak, 2010;Fang et al, 2010;Bošeľa et al, 2011;Bošeľa et al, 2014;Dittmar et al, 2012;Hökkä et al, 2012), and studies using more than two cores or discs are less frequent (e.g. Brienen and Zuidema, 2005;Ďurský et al, 2006;Van Der MaatenTheunissen et al, 2013) because they are costly and destructive.…”
Section: Introductionmentioning
confidence: 99%